The effect of a new structured motivational interview model on diet and exercise behaviors in type 2 diabetes patients at primary care: a randomized controlled study - AKMAN, MEHMET (My University, 2023)
Objectives: In this study, it was aimed to evaluate the effect of structured short motivational interviewing in exercise and diet-related behavioral changes in type 2 diabetes patients in primary care. Methods: Participants were divided into control and intervention groups. The study was single-blinded, and only the researchers knew the participants in each group. The intervention group received a motivating interview- based intervention a total of 4 times in the 1st month of the study and followed up in the 3rd month. The control group was followed by family physicians and evaluated at 3 months without any motivational intervention. One-week pedometer, international physical activity questionnaire (IPAQ2) scores, daily calorie intake, EuroQol (EQ5D), multidimensional diabetes questionnaire (MDQ), and motivational assessment scale were used at the beginning of the study and the 3rd-month follow-up. Results: The study included 84 (51.5%) participants in the intervention group and 79 (48.5%) patients in the control group. There was a significant difference between the control and intervention groups in terms of a 1-week pedometer (2785.0 [1002.0-7240.0] step/day vs. 5231.0 [1364.0-11827.0] step/day, p<0.001), IPAQ2 scores (0.0 [0.0-1056.0] vs. 495.0 [0.0-1396.0], p<0.001), EQ5D scale total scores (5.0 [5.0-10.0] vs. 5.0 [5.0-8.0], p=0.006), and MDQ scale total scores (607.0 [244.0-847.0] vs. 730.0 [235.0-847.0], p<0.001) at the 3rd-month follow-up. Conclusion: A structured motivational interviewing model is an effective tool for developing lifestyle changes in type 2 diabetes mellitus patients.
Keywords: Tıp; Sosyal ve Beşeri Bilimler; Sosyoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Social Sciences and Humanities; Sociology; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; TIP, GENEL & DAHİLİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; MEDICINE, GENERAL & INTERNAL; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Halk, Çevre ve İş Sağlığı; Aile Sağlığı; Public Health, Environmental and Occupational Health; Family Practice; Lifestyle; motivational interviewing; type 2 diabetes mellitus; Lifestyle; motivational interviewing; type 2 diabetes mellitus